1997
DOI: 10.1007/s004290050087
|View full text |Cite
|
Sign up to set email alerts
|

Retinotopic order in the optic nerve and superior colliculus during development of the retinocollicular projection in the wallaby ( Macropus eugenii )

Abstract: Retinotopic order of optic axons in the optic nerve and superior colliculus of the marsupial mammal, the wallaby (Macropus eugenii), has been examined and compared during development of the retinocollicular projection to investigate the role of order in the nerve in map formation. Small groups of axons from different retinal quadrants were labelled in vivo with a carbocyanine dye from just after axons first reached the colliculus to when the projection was mature. The distribution and branching patterns of axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 74 publications
1
34
0
Order By: Relevance
“…The ages examined spanned the period when retinal axons are growing into and forming connections in the SC (Mark et al, 1993a; Ding and Marotte, 1996, 1997). At P12–17, retinal axons are growing into both the ipsilateral and contralateral SC in coarse retinotopic order and by P25–33 have fully covered the contralateral SC although arborisation has not commenced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ages examined spanned the period when retinal axons are growing into and forming connections in the SC (Mark et al, 1993a; Ding and Marotte, 1996, 1997). At P12–17, retinal axons are growing into both the ipsilateral and contralateral SC in coarse retinotopic order and by P25–33 have fully covered the contralateral SC although arborisation has not commenced.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the in situ hybridisation data which showed retinotopically corresponding high ventral to low dorsal gradients of Ten‐m3 mRNA expressed in retinal ganglion cells, and high medial to low lateral gradients of Ten‐m3 within the retinorecipient layers of the SC. This suggests that retinal ganglion cell afferents form connections with target cells in the SC that express Ten‐m3 at similar relative levels: the ventral retina which expressed higher levels of Ten‐m3 than dorsal retina connects with medial SC (Mark et al, 1993b; Ding and Marotte, 1997) which also expressed higher levels than lateral SC. Results from the in situ hybridisation experiments revealed that the gradients were more pronounced in younger age groups, with one of the younger age groups (P27–37) showing the greatest fold differences in qPCR data in regional expression in both the retina and SC.…”
Section: Discussionmentioning
confidence: 99%
“…Invasion of the superior colliculus by retinocollicular axons appears to coincide with the initial development of laminar cytoarchitecture in the superior colliculus and the appearance of strong GAP-43 ir in rostrocaudally running fibers in the superficial layers, where these axons are located (Ding and Marotte 1997). A more complex laminar specific pattern of GAP-43 ir fibers appears by P19, but the deeper fibers seen at that time are probably from sources other than the retina.…”
Section: Development Of the Superior Colliculus: The Relationship Betmentioning
confidence: 83%
“…The influence can be ignored. The relationship between stimulating patterns and the position, size and shape of phosphene are also not clear [14]. The distribution of electric field of electrode is an important factor to evaluate the stimulation effect.…”
Section: Discussionmentioning
confidence: 99%